2016
DOI: 10.1002/ange.201603395
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction: Structure of the Liquid–Liquid Interface Containing a Diamide Ligand

Abstract: Knowledge of the (supra)molecular structure of an interface that contains amphiphilic ligand molecules is necessary for af ull understanding of ion transfer during solvent extraction. Even if molecular dynamics already yield some insight in the molecular configurations in solution, hardly any experimental data giving access to distributions of both extractant molecules and ions at the liquid-liquid interface exist. Here,t he combined application of X-raya nd neutron reflectivity measurements represents ak ey m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Scattering contrast arises from a difference between the SLDs of neighboring media. Reflectometry studies with a focus on the structure of bare interfaces between water and hydrophobic media are often carried out with two types of experimental configurations offering strong contrast between the two bulk media, as schematically illustrated in Figure 1A: (i) Hydrogenous or deuterated water (H2O or D2O, respectively) or mixtures thereof contacting air or gas [33,42,43], or (ii) H2O or D2O contacting hydrogenous hydrocarbon chains in the form of oil [5,34,35,36,37,38,39,40,41] or of oil-like molecules grafted to a solid surface [44]. Contrast-optimized NR studies dealing with hydrophobized solids [45,46,47] involved considerable structural complexity, making interpretation difficult in view of the limited Qz-range [46].…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Scattering contrast arises from a difference between the SLDs of neighboring media. Reflectometry studies with a focus on the structure of bare interfaces between water and hydrophobic media are often carried out with two types of experimental configurations offering strong contrast between the two bulk media, as schematically illustrated in Figure 1A: (i) Hydrogenous or deuterated water (H2O or D2O, respectively) or mixtures thereof contacting air or gas [33,42,43], or (ii) H2O or D2O contacting hydrogenous hydrocarbon chains in the form of oil [5,34,35,36,37,38,39,40,41] or of oil-like molecules grafted to a solid surface [44]. Contrast-optimized NR studies dealing with hydrophobized solids [45,46,47] involved considerable structural complexity, making interpretation difficult in view of the limited Qz-range [46].…”
Section: Results and Discussionmentioning
confidence: 99%
“…For XRR experiments, MilliQ water (H2O, MilliQ® Integral ultrapure water Type 1, specific resistance ≥ 18.2 normalMΩ·cm, organic content ≤ 5 ppb) from a standard laboratory source was used. The liquid/liquid cells for XRR and NR [5,39,40] were cleaned by washing with organic solvents (chloroform, acetone, ethanol) and by plasma cleaning. Subsequently, the lower part of the liquid pool was rendered hydrophobic via covalent functionalization with octadecyltrichlorosilane (OTS) by exposure to a freshly-prepared solution of OTS in anhydrous toluene at a concentration of 1 mM for 30 min.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular mechanism of the ion transport from an aqueous to an organic phase taking place at an aqueous-organic interface has been studied by a combination of XRR with neutron reflectivity [180]. It was shown that hard trivalent cations can be repelled or attracted by the extractant-enriched interface according to the nature of the ligand [181]. The process of metal ion extraction starts with hydration of ions in the aqueous phase, which are then transformed at the aqueous-organic interface into supramolecular complexes in the form of an inverted bilayer that dissolves in the oil phase.…”
Section: Liquid Interfacesmentioning
confidence: 99%